NEW OPPORTUNITIES IN TREATMENT OF CHRONIC HEART FAILURE WITH NORMAL EJECTION FRACTION - A. G. Dushina; R. A. Libis (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To evaluate aim worthiness and efficacy of the application of angiotensin type II receptor blockers (ARB) and calcium channel antagonists (CCA) in patients with early stages of chronic heart failure with normal ejection fraction (CHF-NEF) developed on the background of arterial hypertension and arterial hypertension with ischemic heart disease. Material and methods. Totally 67 patients included with CHF-NEF (EF>50%), of I-IIA stage, I-III functional class (FC), developed over arterial hypertension and arterial hypertension with ischemic heart disease. Depending on the specifics of treatment patients were selected into 2 groups: main (n=37) group— taking ARBs (valsartan, average dosage 130,8±38,8mg/ day) and CCA (S(-) amlodipine, average dosage 3,2±1,1 mg/day) with the standard therapy of CHF, and control group (n=30) taking only standard treatment. Investigation in all patients took place before the beginning of treatment and in 12 weeks and included anamnesis, examination, electrocardiography and Holter monitoring, echocardiography, 6-minute test (SMT), evaluation of CHF severity by the score of clinical condition (SCC), evaluation of life quality with Minnesota Questionnaire for Heart failure. Results. Intergroup analysis showed that the improvement of clinical condition by the SCC in the main group was -50,0 [-50,0; -31,0]%, in control group — -33,3 [-33,3; 0,0]% (р<0,05), SMT exercise tolerance — 11,6±8,4 and 6,6±10,6% (р<0,05), life quality -26,0 [-44,0; 0,0] and -26,8 [-33,3; -18,2]% (р>0,05), respectively. Among echocardiographic parameters only decrease of interventricular septum thickness was marked in both groups — -4,0±1,2 and -2,9±1,5%, resp., (р<0,05). Conclusion. Usage of ARB valsartan and CCA (S-) amlodipine in patients with earlier stages of CHF-NEF leads to more serious regression of myocardial hypertrophy of the left ventricle, the decrease of clinical symptomatic severity, improvement of exercise tolerance.